1999
DOI: 10.1037/0022-006x.67.3.374
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative affectivity in children: Confirmatory factor analysis of a two-factor model and its relation to symptoms of anxiety and depression.

Abstract: The positive affect (PA) and negative affect (NA) framework that is embodied in the tripartite model of anxiety and depression has proved useful with adult populations; however, there is as yet little investigation with children concerning either the measurement of PA and NA or the relation between PA and NA and levels of adjustment. A confirmatory factor analysis was used in this study to examine the structure of self-reported affect and its relation to depressive and anxious symptoms in school children (4th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
160
3
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(197 citation statements)
references
References 89 publications
29
160
3
3
Order By: Relevance
“…The 15 items on the NA scale were summed, meaning that higher values indicate greater negative emotions. Adequate internal reliability and good convergent and discriminant validity have been demonstrated with comparisons to well-established self-report measures and clinical diagnoses of depression and anxiety (Joiner & Lonigan, 2000;Laurent et al, 1999;Lonigan, Hooe, David, & Kistner, 1999). Sufficient internal consistency was found for the NA Scale (Cronbach's αs of .88 and .87) at two time points within this investigation.…”
Section: Positive and Negative Affect Scale For Children (Panas-c)mentioning
confidence: 55%
“…The 15 items on the NA scale were summed, meaning that higher values indicate greater negative emotions. Adequate internal reliability and good convergent and discriminant validity have been demonstrated with comparisons to well-established self-report measures and clinical diagnoses of depression and anxiety (Joiner & Lonigan, 2000;Laurent et al, 1999;Lonigan, Hooe, David, & Kistner, 1999). Sufficient internal consistency was found for the NA Scale (Cronbach's αs of .88 and .87) at two time points within this investigation.…”
Section: Positive and Negative Affect Scale For Children (Panas-c)mentioning
confidence: 55%
“…Studies using self-report measures have indeed shown that anhedonia and blunted behavioral activation predicted (1) future depressive symptoms (Hundt et al, 2007;Kimbrel et al, 2007), (2) course of depression and time to recovery (McFarland et al, 2006), and (3) poor treatment outcome 8-12 months later (Kasch et al, 2002;Spijker et al, 2001). Moreover, low positive affect has been identified as a risk factor for the development and maintenance of depressive symptoms in children (Hayden et al, 2006;Joiner and Lonigan, 2000;Lonigan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for a higher order factor that explains the presence of different types of anxiety has been found in children (Nauta et al, 2004) and adults (Hettema et al, 2005;Krueger, 1999;Vollebergh et al, 2001). Negative affectivity (NA) (Chorpita, 2002;Clark, 2005;Clark & Watson, 1991;Lonigan et al, 1999Lonigan et al, , 2003 may be one of the higher order factors that may explain the finding of heterotypic continuity. NA represents displeasurable engagement with the environment and a sense of high subjective distress (Lonigan et al, 2003), and is often considered as a temperament trait that is associated not only with anxiety, but with depression as well (Clark, 2005).…”
Section: Introductionmentioning
confidence: 99%